Penerapan Teknologi Augmented Reality Sebagai Media Pengenalan Noken Papua Berbasis Android - Suci Pebriani Rusanti Sari; Dahliyusmanto Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Noken is the one of the variety handicraft in Indonesia from Papua. Noken is listed on UNESCO as an Indonesian culture heritage that must be preserved. Augmented Reality (AR) technology can beimplemented into an interactive application, so it can increase people attractiveness to know and to introduce Indonesian traditional handicrafts to the world. Commonly, AR application uses special marker so that application can be run (Marker Based Tracking). The use of these markers makes the application inflexible, because only certain marker which already uploaded by programmer on database system can be used. The research’s goal is to present noken in an application by showing3D object and video about noken on AR environment without using special marker. This application is created with Unity 3D and Vuforia by using Markerless User Defined Target (UDT). Moreover,some tools are also needed as supporting tools, like as Adobe Photoshop for interface designing, Adobe Premier for video editing, and Blender for creating noken 3D object. The final result of thisresearch is AR application for android with UDT technique which capable to show 3D object and video above real marker selected by user after detected by smartphone camera. The resultingapplication is alsoequipped with interactive features like scale and rotate. So this application can be used as alternative for conserving and spreading Papua handicraft in interesting and flexible way.Keywords :Augmented Reality (AR), User Defined Target (UDT), Android, Noken 3D object, video about noken